Modulation of the functions of myeloid‐derived suppressor cells : a new strategy of hydrogen sulfide anti‐cancer effects. (27th November 2019) - De Cicco, Paola; Ercolano, Giuseppe; Rubino, Valentina; Terrazzano, Giuseppe; Ruggiero, Giuseppina; Cirino, Giuseppe; Ianaro, Angela
Abstract : Background and Purpose: Myeloid‐derived suppressor cells (MDSCs) represent a major obstacle to cancer treatment, as they negatively regulate anti‐tumour immunity through the suppression of tumour‐specific T lymphocytes. Thus, the efficacy of immunotherapies may be improved by targeting MDSCs. In this study, we assessed the ability of hydrogen sulfide (H2 S), a gasotransmitter whose anti‐cancer effects are well known, to inhibit the accumulation and immunosuppressive functions of MDSCs in melanoma. Experimental Approach: Effects of H2 S on the host immune response to cancer were evaluated using an in vivo syngeneic model of murine melanoma. B16F10‐melanoma‐bearing mice were treated with the H2 S donor, diallyl trisulfide (DATS) and analysed for content of MDSCs, dendritic cells (DCs) and T cells. Effects of H2 S on expression of immunosuppressive genes in MDSCs and on T cell proliferation were evaluated. Key Results: In melanoma‐bearing mice, DATS inhibited tumour growth, and this effect was associated with a reduction in the frequency of MDSCs in the spleen, in the blood as well as in the tumour micro‐environment. In addition, we found that CD8 + T cells and DCs were increased. Furthermore, DATS reduced the immuno‐suppressive activity of MDSCs, restoring T cell proliferation. Conclusions and Implications: The H2 S donor compound, DATS, inhibited the expansion and the suppressive functions of MDSCs, suggesting a novel role for H2 S as a modulator of MDSCs in cancer. Therefore, H2 S donors may provide a novel approach for enhancing the efficacy of melanoma immunotherapy. Linked Articles: This article is part of a themed section on Hydrogen Sulfide in Biology & Medicine. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.4/issuetoc